Perception of flower beds in public green areas - Poje, Miroslav; Han Dovedan, Ines; Vukelić, Anton (2013)
Flower beds are one of the aesthetically most striking elements of public green areas. Regardless of such an important role, there is very little research dealing with flower beds as an individual element in space. Research is most oft en based on studying flower species in a broader context. This research tried to ascertain to what extent citizens and professionals perceive flower beds in their everyday lives. Results show that more than half of the subjects notice flower beds on a daily basis. Furthermore, statistically significant differences were determined in the professionals’ and nonprofessionals’ knowledge of certain locations in which flower beds are present, and in their tendency to participate in projects involving the design and maintenance of flower beds. Namely, professionals are more acquainted with the locations of flower beds, and are more likely to participate in a project involving the design and maintenance of flower beds. Results point to the importance of flower beds and the need for further research of their role as a part of urban green spaces.
Projekt MZOS
ENG